2021
DOI: 10.1186/s13089-021-00236-4
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound training and evaluation for proficiency among physicians in a low-resource setting

Abstract: Background Lung ultrasound (LUS) is helpful for the evaluation of patients with dyspnea in the emergency department (ED). However, it remains unclear how much training and how many LUS examinations are needed for ED physicians to obtain proficiency. The objective of this study was to determine the threshold number of LUS physicians need to perform to achieve proficiency for interpreting LUS on ED patients with dyspnea. Methods A prospective study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…For education and training purposes, LUS can further be broken down into modalities with basic to advanced level qualification 280 . Learning curves may be described as steep 281 . Furthermore, it has been shown that the application of LUS by different non‐physician professions such as physiotherapists 282 or paramedics is feasible 283,284 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For education and training purposes, LUS can further be broken down into modalities with basic to advanced level qualification 280 . Learning curves may be described as steep 281 . Furthermore, it has been shown that the application of LUS by different non‐physician professions such as physiotherapists 282 or paramedics is feasible 283,284 …”
Section: Methodsmentioning
confidence: 99%
“…280 Learning curves may be described as steep. 281 Furthermore, it has been shown that the application of LUS by different non-physician professions such as physiotherapists 282 or paramedics is feasible. 283,284 Educational science assessing LUS proficiency longitudinally from "zero" to independent clinical competence will be hard to acquire.…”
Section: Guidelinesmentioning
confidence: 99%
“…Treatment accounted for the bulk of management changes (83.3%), followed by disposition (13.3%), and new consultations (2.7%). This study found that bedside lung ultrasonography had a significant impact on physician clinical decision-making, particularly in terms of patient diagnosis and treatment, in an emergency department in Nepal (4).…”
Section: Introduction/backgroundmentioning
confidence: 77%
“…It is also possible that lung US was performed and recorded as a component of indicated BELS scans. The use of this particular modality is well‐supported by literature demonstrating the ease of skill acquisition 19 and a growing evidence base to support its accurate findings, especially in patients with undifferentiated dyspnoea, 11 , 20 heart failure 10 or pneumonia. 21 This finding opens an opportunity for POCUS educators to emphasise the ease with which lung US can be both learnt and applied to a wide variety of clinical circumstances in the ED.…”
Section: Discussionmentioning
confidence: 93%